Kilka uwag o roli ocen etycznych w prawie cywilnym - Pajor, Tomasz (Annales. Etyka w Życiu Gospodarczym, 2009)
Civil law norms give a considerable space for ethical value judgments. In this respect, the key role is played by the provisions called “general clauses” that refer to extra-juridical value judgments and oblige to take them into account in the process of deciding in civil law cases. The purpose of such clauses is to ensure the necessary flexibility of law and to influence the shaping of proper human relations. In the field of economic activity they are to favour the attitudes of honesty, of mutual trust and of readiness to serve others – the values which constitute a basis for the system of free market competition. A separate question is how to realize these assumptions in the practice of adjudicating which remains the task of courts and tribunals and their case law.